Potential of calcium nitrate to mitigate the aluminum toxicity in Phaseolus vulgaris effects on morphoanatomical traits, mineral nutrition and photosynthesis - Vasconcelos, Camila Vilela (Ecotoxicology (London, England), 2020)
Common bean (Phaseolus vulgaris) cultivation occurs mainly in regions with acidic soils, where high aluminum (Al) concentration is a major constraint to crop production. In this study, we evaluated tolerance and sensitivity traits to Al exposure and calcium (Ca) deficiency in bean plants, and determined the efficiency of Ca to mitigate the toxic Al effects. Two bean cultivars (BRS Estilo and Campos Gerais) were grown in three soil conditions: (I) soil liming with calcium hydroxide Ca(OH)2 and Al unavailable (-Al+Ca); (II) fertilized soil with calcium nitrate [Ca(NO3)2·4H2O] and Al available (+Al+Ca); and (III) soil without Ca addition and Al available (+Al-Ca). At the beginning of the reproductive stage, we evaluated the photosynthetic processes, mineral nutrition, and leaf anatomy and morphological traits of plants. The photosynthetic parameters were good tools for monitor Al sensitivity in bean. +Al+Ca soil treatment mitigated the deleterious effects of Al on growth and mineral nutrition of both bean cultivars. However, Ca did not prevent the toxic effects of Al on leaf anatomy. Al stress and Ca deficiency caused negative effects on nutrient content, photosynthetic activity and leaf anatomy of bean plants. Calcium mitigated Al toxicity, primarily in the Campos Gerais cultivar, showing the potential to improve bean crop productivity in acid soils